2006
DOI: 10.1108/01425450710714469
|View full text |Cite
|
Sign up to set email alerts
|

Line managers’ views on adopting human resource roles: the case of Hilton (UK) hotels

Abstract: PurposeThe purpose of this paper is to explore different levels of line manager perspectives, namely strategic and first‐line on their role in human resource management (HRM) and human resource development (HRD), and to identify enablers of and barriers to devolving HR to line managers.Design/methodology/approachUsing a deductive approach, case study data was collected from 76 hotels, owned by Hilton UK, via self‐administered questionnaires to strategic and first‐line managers. Descriptive statistics were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 31 publications
3
56
0
1
Order By: Relevance
“…This might explain the reason why LMs at Airport X demanded more support to perform their HRM role. The results corroborate the findings of much previous work regarding the importance of support for LMs for their HRM role (Cunningham & Hyman, 1995;Floyd & Lane, 2000;Renwick, 2003;Watson, et al, 2007). Slow and inconsistent feedback from HR specialists was not surprising, as prior studies have reported frustration among LMs not receiving sufficient and consistent support from key members in the organization, including HR specialists (Cunningham & Hyman, 1995;Whittaker & Marchington, 2003).…”
supporting
confidence: 81%
“…This might explain the reason why LMs at Airport X demanded more support to perform their HRM role. The results corroborate the findings of much previous work regarding the importance of support for LMs for their HRM role (Cunningham & Hyman, 1995;Floyd & Lane, 2000;Renwick, 2003;Watson, et al, 2007). Slow and inconsistent feedback from HR specialists was not surprising, as prior studies have reported frustration among LMs not receiving sufficient and consistent support from key members in the organization, including HR specialists (Cunningham & Hyman, 1995;Whittaker & Marchington, 2003).…”
supporting
confidence: 81%
“…On the other hand, (Renwick, 2003) postulated that HRM is a "centre stage" role for line managers and there could be many reasons for this like decentralization, which have been cited as rightsizing, restructuring and an increased need to put emphasizes on employees inputs in order to improve organizational performance (Gibbs & Renwick, 2003). In fact, line managers play a significant role in creating a positive influence on employee commitment ISSN 2162-3058 2016 and engagement and ultimately, business performance (Watson & Maxwell, 2006) for e.g (Cunningham & Hayman, p.9, 1999) emphasized the role of line managers in promoting an "integrative culture of employee management through line management". A recent report of (CIPD, 2006) indicates that line manager"s intervention in various aspects of employee development such as coaching, communication, empowering employees, developing an organizational culture, work engagement and involvement has a positive impact on the overall organizational performance (Hutchinson & Purcell, 2003).…”
Section: Examining the Nature Of Link: Line Managers" Intervention Inmentioning
confidence: 99%
“…The line managers' involvement factors in HR initiatives can be seen in the devolution of the HR function to line managers (Watson et al, 2007). There are three factors that are evaluated, which are the relationship with HR specialists, organizational support, and commitment of line managers.…”
Section: Line Manager Involvement Factors In Hr Initiativesmentioning
confidence: 99%
“…Line managers play an important role in practicing HR initiatives, because they are the responsible managers for implementing HR practices in the production of products or the provision of services (Qadeer, Shafique & Rehman, 2011;Watson, Maxwell & Farquhason, 2007). HR initiatives such as training have always been considered as one of line managers' job (Papalexandris & Panayotopoulou, 2005).…”
Section: Line Managers Issues In Human Resourcesmentioning
confidence: 99%